Slc26a7 chloride channel activity and localization in mouse Reissner’s membrane epithelium - Kim, Kyunghee X.; Sanneman, Joel D.; Kim, Hyoung-Mi; Harbidge, Donald G.; Xu, Jie; Soleimani, Manoocher; Wangemann, Antje Philine; Marcus, Daniel C. (My University, 2014)
Several members of the SLC26 gene family have highly-restricted expression patterns in the auditory and vestibular periphery and mutations in mice of at least two of these (SLC26A4 and SLC26A5) lead to deficits in hearing and/or balance. A previous report pointed to SLC26A7 as a candidate gene important for cochlear function. In the present study, inner ears were assayed by immunostaining for Slc26a7 in neonatal and adult mice. Slc26a7 was detected in the basolateral membrane of Reissner’s membrane epithelial cells but not neighboring cells, with an onset of expression at P5; gene knockout resulted in the absence of protein expression in Reissner’s membrane. Whole-cell patch clamp recordings revealed anion currents and conductances that were elevated for NO[subscript 3]ˉ over Clˉ and inhibited by Iˉ and NPPB. Elevated NO[subscript 3]ˉ currents were absent in Slc26a7 knockout mice. There were, however, no major changes to hearing (auditory brainstem response) of knockout mice during early adult life under constitutive and noise exposure conditions. The lack of Slc26a7 protein expression found in the wild-type vestibular labyrinth was consistent with the observation of normal balance. We conclude that SLC26A7 participates in Clˉ transport in Reissner’s membrane epithelial cells, but that either other anion pathways, such as ClC-2, possibly substitute satisfactorily under the conditions tested or that Clˉ conductance in these cells is not critical to cochlear function. The involvement of SLC26A7 in cellular pH regulation in other epithelial cells leaves open the possibility that SLC26A7 is needed in Reissner’s membrane cells during local perturbations of pH.
Keywords: Mouse; SLC26 gene family; Reissner’s membrane; Cochlear function